Um estudo sobre o cálculo operatório no campo multiplicativo com alunos de 5ª série do ensino fundamental - Bonanno, Aparecida de Lourdes (2007)
This research has the objective of investigating the operative calculation in the multiplicative field with a group of students of 5th series of the Fundamental Teaching, trying identify those students' knowledge about two great learning expectations: the first one includes the analysis, the interpretation, and the resolution of problem s situation with the different meanings of the multiplication and division and the second one is the acting of the students' group in mental- calculations and written, exact or approximate - through varied strategies. It leans on the contributions of different authors' , especially, Gerard Vergnaud, Constance Kamii and Irma Saiz.To accomplish this study, firstly we made a bibliographical rising and the analysis of an official curricular document and later we organized data collection instruments, containing activities and calculations to be proposed for a one group with 21 students of 5th series, of a state public school, allowing a diagnostic study with that group. After developing the treatment of the collected data and of elaborating our analyses, we accomplished interviews with some students to enlarge our understanding on the subject. In general, we observed that the conventional algorithms are still the procedures more used by the students in the situations problem and written calculation, but an interesting and positive fact is what many students use procedures don't stipulate to solve the situations problem. We still verified the importance of to consider and to explore, in the teaching, the several strategies don't stipulate established by the students in several situation-problem